Evaluating the Potential Association between Prenatal Exposure to Testosterone and Criminal Involvement and Criminogenic Traits - Joyner-Carpanini, Bridget (American journal of criminal justice, 2021)
Criminologists have long been interested in understanding the mechanisms that create male-female differences in criminal involvement. One possible explanation that has generated a significant amount of interest is whether testosterone—including exposure to prenatal testosterone—might be central to male-female disparities in crime. We use this possibility as a springboard to examine the potential association between prenatal testosterone and multiple criminogenic outcomes. To do so, we analyze a sample of female dizygotic twin pairs drawn from the National Longitudinal Study of Adolescent to Adult Health and employ a proxy measure of prenatal testosterone based off of the twin testosterone transfer (TTT) hypothesis. The analyses revealed that prenatal testosterone is not associated with nonviolent criminal involvement, violent criminal involvement, psychopathic personality traits, being arrested, and being incarcerated. Interestingly, there was a small association with low self-control, but the effect was in the opposite direction of expectations. We conclude by discussing the implications and limitations of our study as well as considerations for future research.